EFFECT OF TYPE OF FREEZING ON THE FUNCTIONAL CHARACTERISTICS OF FROZEN THAWED BULL SPERMATOZOA - NAGENDRAKUMAR, S B; KATHIRESAN, D (The Indian Journal of Animal Reproduction, 2023)
Programmable biological freezers can be used to control and optimize the freezing rate for successful cryopreservation of bull spermatozoa. The effect of freezing methods on the functional characteristics of frozen thawed bull spermatozoa was studied. Semen samples collected from Jersey cross (n=6) and Friesian cross (n=6) bulls were extended in Tris egg citric acid diluent. The samples were split and cryopreserved using static vapor freezing and programmed freezing. In both the methods of cryopreservation the post-thaw semen showed a highly significant (P<0.01) reduction in the functional characteristics such as progressive motility, acrosome status and membrane integrity. The post-thaw motility and percentage of intact acrosome were more in programmed freezing (P<0.01) than the static vapor freezing. Anon-significant increase in hypo-osmotic swelling response and percentage of live spermatozoa with intact acrosome were obtained in the programmed freezing. The release of enzyme Aspartate transaminase into the seminal plasma was lower in the programmed freezing than in the static vapor freezing . The hypo-osmotic swelling test was relatively easy to perform and was simple, economical and efficacious in assessing the membrane integrity of bovine spermatozoa. The supravital triple staining technique was useful in simultaneous assessment of both membrane integrity and acrosome status of bull spermatozoa. It is evident from the present investigation that the programmed freezing results in enhanced post-thaw motility, acrosome retention and membrane integrity and might be adopted in frozen semen production.